(untitled) (The Pakistan Development Review, 2008)
There is convincing evidence that Pakistan has entered the demographic bonus phase; child dependency is declining and youth share in the total population is rising. This paper has examined youth employment in the context of demographic transition evidenced since the early 1990s. Changes in the level of educational attainment have also been analysed. The study has used the data from Pakistan Demographic Surveys and Labour Force Surveys carried out between 1990 and 2005. Findings of the study show that the benefits of demographic transition in terms of rising share of youth in the total population has partially been translated through development of their human capital and productive absorption in the local labour market. While the pace of human capital formation seems to be satisfactory in urban Pakistan, it is dismal in rural areas, particularly for females. High levels of both female inactivity across the education categories and unemployment for males as well as females urge a strong youth employment policy in Pakistan to reap the benefits of the ongoing demographic transition. Youth are a source of development, and a high priority may be placed on preparing them with the skills needed for their adjustment in the labour market.